Same-sex parenting in Brazil and Portugal: An integrative review (Research, Society and Development, 2022)
This integrative review aimed to analyze and systematize the knowledge produced on parenting by same-sex couples in the Brazilian and Portuguese contexts until 2019. We sought to describe the main topics in scientific production in empirical articles in both countries and highlight advances and/or gaps in the discussions. The databases searched were LILACS, Redalyc, RCAAP, PePSIC, SciELO and EBSCOhost. The searches occurred in 2020, with seven descriptors in Portuguese and their respective translations into English, resulting in 17 different search combinations. Fifty-three articles were retrieved: 35 Brazilian, 17 Portuguese and 1 Luso-Brazilian. We observed standards in the scientific production on the theme and analyzed the material qualitatively through Thematic Analysis. All the articles surveyed presented a cross-sectional design, with a prevalence of qualitative studies in Brazil and quantitative studies in Portugal. It was verified, in both countries, the desire, the achievement and the experience of parenting, the challenges faced by families and the parental practices exercised with the children. Low social support and coping with prejudice related to LGB-phobia were identified. Although the conceptions about parenting exercised by same-sex couples and its benefits for child development have been positive for a significant portion of the Brazilian and Portuguese population, negative opinions were present in both countries, especially among older, male, religious and more conservative people. We highlight the need to expand the discussion on family and diversity in society, academia, and the training and updating of social network professionals.